Green feed in the marine fish farming - Jansson, Therese A.M. (2010)
Global catch fishery is said to been oppressed to its limit (Boyd & Schmittou, 1999), further implying aquaculture might be the only solution to the world demand for fishery products. The applied term aquaculture in this paper refers to the one used by NOAA (2008); breeding, rearing, and harvesting of plants and animals in all kind of water environments, including but not limited to ponds, rivers, lakes, and the ocean.